2013
DOI: 10.3109/02713683.2013.827212
|View full text |Cite
|
Sign up to set email alerts
|

Association of TLR2 and TLR4 Gene Single Nucleotide Polymorphisms with Fungal Keratitis in Chinese Han Population

Abstract: The rs10983755, located in the 5'-untranslated region (UTR) of TLR4, was most strongly associated with FK of Chinese Han population (p < 0.05). The analysis of TLR2 gene polymorphisms showed no significant association upon FK susceptibilities of Chinese Han population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 27 publications
0
3
0
1
Order By: Relevance
“…Різноспрямований характер зв'язку одиночних нуклеотидних поліморфізмів (SNP), які розташовані в генах TLR2 і TLR4, з виникненням грібкового кератиту також показано у популяції Хань [16]. Найбільши зв'язок було показано для rs10983755 TLR4, що розташований у 5'-нетрансльованій області (UTR) гена.…”
Section: результати та їх обговоренняunclassified
“…Різноспрямований характер зв'язку одиночних нуклеотидних поліморфізмів (SNP), які розташовані в генах TLR2 і TLR4, з виникненням грібкового кератиту також показано у популяції Хань [16]. Найбільши зв'язок було показано для rs10983755 TLR4, що розташований у 5'-нетрансльованій області (UTR) гена.…”
Section: результати та їх обговоренняunclassified
“…Mucormycosis frequently co-occurs with aspergillosis ( Alfano et al, 2006 ; Tsikala-Vafea et al, 2020 ; Johnson et al, 2021 ; Zayet et al, 2021 ). SNPs in PRRs like Toll-like receptors (TLRs) have already been associated with increased susceptibility to fungal infections ( Bergantim et al, 2013 ; Wang et al, 2013 ; Fischer et al, 2016 ; Zhang et al, 2019 ; Aqsa et al, 2020 ). The TLR2 SNP rs5743708 (R753Q, GA/AA genotype, n = 12) is associated with a higher risk of pneumonia and invasive fungal infections in patients with acute myeloid leukemia undergoing chemotherapy ( Fischer et al, 2016 ).…”
Section: Current Aspects In Diagnosis and Prediction Of Other Fungal ...mentioning
confidence: 99%
“…The TLR2 SNP rs5743708 (R753Q, GA/AA genotype, n = 12) is associated with a higher risk of pneumonia and invasive fungal infections in patients with acute myeloid leukemia undergoing chemotherapy ( Fischer et al, 2016 ). TLR with SNP’s have previously been associated with increased susceptibility to fungal infections ( Wang et al, 2013 ; Fischer et al, 2016 ). TLR2 SNP rs5743708 (R753Q, GA/AA genotype, n = 12) is associated with a higher risk of pneumonia and invasive fungal infections in patients with acute myeloid leukemia receiving chemotherapy ( Fischer et al, 2016 ).…”
Section: Current Aspects In Diagnosis and Prediction Of Other Fungal ...mentioning
confidence: 99%
“…A study among a Han Chinese population of patients with FK compared controls found a particular TLR4 allele that was associated with an increased risk of developing FK [14].…”
Section: Cytokines and Innate Immunitymentioning
confidence: 99%